Pengaruh Pemberian Pupuk Organik Cair (POC) Dari Limbah Cair Tahu Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) - Maretik Maretik; Mursida Mursida; Yanti Yanti; Fitrianti Handayani; Sutrisnawati Mehora (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
This study aims to determine the effect of tofu liquid waste on the growth of mustard greens (Brassica juncea L.). The method used in this study was a Randomized Block Design (RAK) which consisted of 5 treatment levels and 3 replications to obtain 15 experimental polybags. The results of the ANOVA test for the group showed that the height growth of the mustard greens did not have a significant effect, namely FCount (0.52) FTabel (4.46) and for the treatment did not have a significant effect, namely FHitung (0.27) FTabel (4,46), It is suspected that excess nitrogen will produce young shoots that are soft/weak and vegetative, acidify soil reactions, lower soil pH, and be detrimental to plants because it will bind other nutrients so that it will be difficult for plants to absorb them and fertilization will become less effective and inefficient. The results of the ANOVA test on the number of leaves showed that the treatment of liquid organic fertilizer from tofu liquid waste for groups had a significant effect, namely FHitung (5.39) FTabel (4.46), it was suspected that the amount of nutrients absorbed by plants had an effect on the process of leaf formation because the process of forming new cells is very closely related to the availability of nutrients needed by plants. the results of the ANOVA test on the fresh weight of mustard greens showed that the treatment of liquid organic fertilizer from tofu liquid waste for the group had a significant effect, namely (7,69) FTabel (4,46), as well as treatment had a significant effect (22,83) FTabel (4,46), It is suspected that fertilizer is absorbed optimally so that it can support plant metabolic processes and have a good effect on the growth of fresh weight in mustard greens.